Turn on your mobile devices in the english classes: tweets no processo de escrita colaborativa on-line do gênero personal recount - Vânia Carvalho de Castro (2015)
This research investigated the pedagogical possibilities of Twitter and its resources so as to support the development of online collaborative writing of the genre personal recount in English. This study aims to verify how Twitter and its resources aided students throughout the stages of the writing cyclic process didactic model proposed by Dias (2004), considering the text production conditions (Who is writing, why, about what, to whom, how). Also, this research looked into how the online collaborative text production through tweets contributed with the writing adequacy of the genre personal recount. Finally, it analyzed the aspects related to the pedagogical potential of Twitter to underpin the process of collaborative learning. The didactic procedures that sustained the teaching of the recounts production have emphasized the previous study of the characteristics of the genre, the writing as a process, and the collaborative writing amongst the members of the groups in order to improve their texts. The research has been carried out with a group of students at the Projeto de Ensino de Línguas Estrangeiras CACS (Foreign Language Teaching Project), located in FAFICH on UFMG campus in Belo Horizonte, Minas Gerais. The data collection instruments were two questionnaires, the interactive tweets by students, and their text productions. Based on the research outcomes, it has been concluded that the digital technologies, according to the writing process and literacies or multiliteracies (KALANTZIS E COPE, 2012, 2013), help the development of the writing in foreign language, encourage learners autonomy by establishing their effective participation in the process of production and revision in collaboration with their classmates.